Eco-efficient vapor recompression-assisted pressure-swing distillation process for the separation of a maximum-boiling azeotrope. (1st April 2020) - Shi, Pengyuan; Zhang, Qingjun; Zeng, Aiwu; Ma, Youguang; Yuan, Xigang
Abstract: The feasibility and effectiveness of the intensified vapor recompression-assisted pressure-swing distillation (PSDVRC) arrangements in different separation sequences are explored with separating a maximum-boiling methanol/diethylamine azeotrope as the specific example. The energy-efficient Heat Exchanger Network Synthesis (HENs) option is used to further improve the possible energy recovery in certain arrangement. The globally optimal arrangement is the intensified self-heat recuperative vapor recompression-assisted PSDVRC-FP-HEN process in the low-pressure column (LPC)-to-high pressure column (HPC) sequence. The reductions of 39.33% (13.93%) in total annual cost, 89.12% (81.95%) in carbon footprints, and the improvement of 116.31% (44.71%) in second-law efficiency can be achieved in comparison with the conventional process, wherein, the data in these brackets represent the economically optimal heat-integrated configuration. And the exergy destruction in each component (Sankey diagram) for all eco-efficiently intensified alternatives are obtained. Result shows that the exergy increase in LPC-to-HPC sequence is higher than that of another sequence, along with the major exergy losses generated in columns, and the distribution of the irreversibility for each individual component in the system is approximately identical when the entropy production analysis and exergy analysis are employed. Graphical abstract: Image 1 Highlights: The feasibility and effectiveness of heat pump options are ranked for maximum-boiling azeotrope. Non-splitting arrangement is prevailed in economics and sustainability. The performance of the LPC-to-HPC sequence is more superior. The Sankey diagram shows the exergy losses in each component for all arrangements.